A Retrospective Analysis of Primary Gastrointestinal Non-Hodgkin Lymphomas: Clinical Features, Prognostic Factors and Treatment Outcomes - Tian C (OncoTargets and Therapy, 2020)
Chen Tian, Yueyang Li, Zehui Chen Department of Hematology, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin 300060, People’s Republic of ChinaCorrespondence: Chen Tian Email tcgirl2001@sina.comIntroduction: Primary gastrointestinal non-Hodgkin lymphoma (PGIL) is a rare hematopoietic malignancy with limited data to guide management.Methods: We analyzed the clinical characteristics and survival of 219 newly diagnosed PGIL patients.Results: Our single-center data showed that the incidence rate of primary gastric lymphoma (PGL) was higher than that of primary intestine lymphoma (PIL). Most PGIL was B-cell originated and DLBCL was the most common pathological type both in PGL and PIL group. Univariate and multivariate analysis showed that IPI score and pathology were independent prognostic factors. The overall survival (OS) and progression-free survival (PFS) of patients with MYC rearrangement were much shorter compared to patients without MYC rearrangement indicating that MYC translocation was related to decreased survival. Neither OS nor PFS differed between patients who received chemotherapy with or without surgery. However, patients who received surgery alone had a poor prognosis.Conclusion: Chemotherapy is the front-line treatment for PGIL while surgery was conducted to relieve tumor-related complications or make diagnosis. MYC rearrangement predicted poor prognosis of PGIL patients.Keywords: primary gastrointestinal lymphomas, prognosis, MYC rearrangement